Preventive Efforts of Youth Reproductive Health Problems Through Informative Media: Health Reproductive Pocket Book Based on Local Culture for Parents in Lima Puluh Kota Regency, West Sumatera Province - Helpi Nelwatri (Science and Environmental Journal for Postgraduate, 2018)
This article was the result of study based on the low knowledge of adolescent about reproductive health. Lack of parental involvement in prevention efforts to prevent the adolescent reproductive health problems in Lima Puluh Kota Regency are one of the factors related to the low knowledge of adolescent about reproductive health. Therefore, a manual pocketbook about reproductive health for parents with local culture approach was needed. This study used the research and development method, which used to produce a particular product, and test the effectiveness of the product. The result was the sources of information on adolescent reproductive health in Lima Puluh Kota Regency are close person, health counselor, Integrated Service Post cadres, and mass media. The role of parents was being the first informant and monitoring the development of adolescents reproductive health. Preventive strategy by providing information to adolescents can be given through health education by parents using a reproductive health pocketbook based on local culture approach.